From common rules to best practices in European Civil Procedure - Hess, Burkhard; Kramer, Xandra Ellen (Studies of the Max Planck Institute Luxembourg for International, European and Regulatory Procedural Law, 2017)
From common rules to best practices in European civil procedure: an introduction / Burkhard Hess, Xandra Kramer -- Common rules and best practices from the perspective of the European Commission / Norel Rosner -- Common rules and best practices from the perspective of the European Parliament / Robert Bray -- Harmonizing civil procedure: initial remarks / Remo Caponi -- Approximation of civil procedural law in the European Union / C.H van Rhee -- Do we need harmonisation to achieve harmonious cooperation? / Marta Requejo Isidro -- Harmonious judicial cooperation through harmonisation: (what) can we learn from criminal matters? / Monique Hazelhorst -- Harmonization of civil procedure: is the United States a model for the European Union? / Christopher A. Whytock -- Comments on Christopher A. Whytock, harmonization of EU procedural law: is the US a positive or negative model? / Jan von Hein -- From drafting common rules to implementing electronic European civil procedures: the rise of e-CODEX / Marco Velicogna, Giampiero Lupo -- Taking justice online: developments in England and Wales and their potential influence on European procedural harmonisation / John Sorabji -- Envisioning the next step in e-justice: in search of the key to provide easy access to cross-border justice for all users / Ernst Steigenga, Marco Velicogna -- E-justice, innovation and the EU / Eva Storskrubb -- Litigation costs and procedural cultures: new avenues for research in procedural law / Adriani Dori, Vincent Richard -- Consumer dispute resolution mechanisms: effective enforcement and common principles / Christopher Hodges, Stefaan Voet -- The need for synergies in judicial cooperation and dispute resolution: changes in the European small claims procedure / Pablo Cortés -- Transplanting best practices from ADR mechanisms to court proceedings in cross-border litigation? / Fernando Gascón Inchausti -- How can alternative mechanisms for dispute resolution contribute to judicial cooperation and what is needed to ensure effective enforcement in cross-border cases? / Jolanda Girzl -- The promotion of best practices in European civil procedure: some introductory remarks / Gilles Cuniberti -- European order for payment procedure from the businesses perspective and practice / Karim Mahari -- How can the best practices of legal professionals with judicial cooperation be operationalised to improve mutual trust? / Arturo Picciotto -- Incorporating European uniform procedures into national procedural systems and practice: best practices a solution for harmonious application / Elena Alina Onţanu -- Approximation of procedural law in Europe / Marcel Storme
Keywords: Zivilprozessrecht; Europäische Union